Development of a Method for Rearing Nezara viridula (Heteroptera: Pentatomidae) on a Semi-solid Artificial Diet. Issue 5 (7th October 2021) - Portilla, Maribel; Reddy, Gadi V P
Abstract: A method for rearing the southern green stinkbug, ( Nezara viridula L.) (Heteroptera: Pentatomidae), using a modified lygus semi-solid artificial diet was developed. First to second-instar nymph were reared in a density of 631.5 ± 125.05 eggs per Petri-dish (4 cm deep × 15 cm diam). Second instar to adult were reared in a density of 535.0 ± 112.46 s instar nymphs per rearing cage (43 × 28 × 9 cm). Mating and oviposition occurred in popup rearing cages (30 × 30 cm), each holding 60–90 mixed sex adults of similar age. Adults emerged 35.88 ± 2.13 d after oviposition and survived for an average of 43.09 ± 9.53 d. On average, adults laid 223.95 ± 69.88 eggs in their lifetime, for a total production of 8, 099 ± 1, 277 fertile eggs/oviposition cage. Egg fertility was 77.93% ± 16.28. Egg masses held in petri-dishes had a total hatchability of 79.38% ± 20.03. Mortality of early nymphs in petri-dishes was 0.64% ± 0.12 for the first instar and 1.37% ± 0.45 for second instar. Late nymphal mortality in rearing cages was 1.41% ± 0.10, 3.47% ± 1.27, and 4.72% ± 1.29 for the third, fourth, and fifth instars, respectively. Survivorship from nymphs to adults was 88.48% ± 2.76. Using artificial diet for rearing N. viridula could reduce cost by avoiding time-consuming issues with daily feeding fresh natural hosts and insect manipulation. It could increase reliability and simplicity of bug production, which should facilitate mass rearing of its biological control agents.